Day-1 Competencies for Veterinarians Specific to Health Informatics - Ouyang, Zenhwa Ben; Hodgson, Jennifer Louise; Robson, Elliot; Havas, Kevin; Stone, Elizabeth; Poljak, Zvonimir; Bernardo, Theresa Marie (Frontiers in Veterinary Science, 2021)
In 2015, the American Association of Veterinary Medical Colleges (AAVMC) developed the Competency-Based Veterinary Education (CBVE) framework to prepare practice-ready veterinarians through competency-based education, which is an outcomes-based approach to equipping students with the skills, knowledge, attitudes, values and abilities to do their jobs. With increasing use of health informatics (HI: the use of information technology to deliver healthcare) by veterinarians, competencies in HI need to be developed. To reach consensus on a HI competency framework in this study, the Competency Framework Development (CFD) process was conducted using an online adaptation of Developing-A-Curriculum, an established methodology in veterinary medicine for reaching consensus among experts. The objectives of this study were to 1) create an HI competency framework for new veterinarians; 2) group the competency statements into common themes; 3) map the HI competency statements to the AAVMC competencies as illustrative sub-competencies; 4) provide insight into specific technologies that are currently relevant to new veterinary graduates; and 5) measure panelist satisfaction with the CFD process. The primary emphasis of the final HI competency framework was that veterinarians must be able to assess, select and implement technology to optimize the client-patient experience, delivery of healthcare and work-life balance for the veterinary team. Veterinarians must also continue their own education regarding technology by engaging relevant experts and opinion leaders.